Gender Diversity in Leadership: Its Impact on Transfer Pricing and Tax Avoidance in Multinational Companies - Tasyahadul Fadlatil Laili; Heru Tjaraka (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to demonstrate the influence of transfer pricing on tax avoidance, with Board Gender Diversity as a moderating variable, in multinational companies listed on the Indonesia Stock Exchange (BEI). Methodology/approach: This research adopts a quantitative approach, employing purposive sampling with a total of 425 observations during the period 2017-2022. The data analysis technique utilized is Moderated Regression Analysis (MRA) conducted using SPSS Statistics 25 software. Findings: The research findings indicate that transfer pricing has a positive influence on tax avoidance, and Board Gender Diversity (BGD) weakens the relationship between multinationality and tax avoidance. Meanwhile, the control variables ROA and leverage positively influence tax avoidance. Practical and Theoretical contribution/Originality: This study aims to provide insights to the Directorate General of Taxation as a reference for assessing tax avoidance behaviors conducted by MNCs to prevent fraudulent taxation practices. Research Limitation: The limitations of this study include incomplete data, as some companies did not provide full access to their annual reports to the public, and some only made the latest reports available on their websites. Additionally, many companies that incurred losses were excluded from the sample. Another limitation of this study is the low adjusted R-squared value, which resulted from the selection of objects and the study period.